Life History Strategies, Photosynthesis, and Stress Tolerance in Propagules of Antarctic Seaweeds - Navarro Martinez, Nelso Patricio; Huovinen, Pirjo; Gómez, Iván (My University, 2020)
Reproduction is one of the most important processes to maintain seaweed populations. In general, growth and reproduction of seaweeds depend on environmental cues, such as change in temperature, light, and nutrients. However, the fact that Antarctic waters show a small variation in temperature and nutrient levels over the year, these biological processes depend mainly on variables related to light conditions, especially daylength. This seems to be more obvious in the eulittoral and shallow sublittoral species, because the reproduction and growth coincides with the spring season. However, in species inhabiting the deeper sublittoral zone, reproduction seems to be controlled by a free-running endogenous clock synchronized by the seasonal variation of daylength or by photoperiodisms. Whatever the case, the Antarctic environment imposes physiological constraints to reproductive output, settlement and development of propagules, recruitment, and growth of seaweeds. Early life stages (e.g., spores, gametes, propagules, and plantlets) are extremely shade-adapted and susceptible to environmental stress, such as exposure to UV radiation; however, they are thermally well adapted, at least for short periods of time, allowing them to develop in a highly variable environment. In this chapter, we review the main reproduction strategies that Antarctic seaweeds display to cope with the extreme environment. Additionally, we review recent studies on stress tolerance of early developmental stages from selected species. In scenarios of the changing Antarctic environment due to warming, UV radiation, freshening, and other emergent stressors, the knowledge on adaptive life strategies of early developmental phases can allow us better predicting the fate of seaweed communities.
Keywords: life history stages; photosynthetic light requirements; reproduction; seasonal development; seaweed propagules